PENGARUH SIZE, PROFITABILITAS, PROFILE, LEVERAGE DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Dewi Yulfaida; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2012)
The motivation of this research about corporate social responsibility disclosure is due to a difference in the results of research (research gap) conducted by several previous studies. The purpose of this study is to empirically examine whether the size, profitability, profile, Leverage and the size of the commissioners board affect the disclosure of social responsibility in manufacturing companies that go public in Indonesia Stock Exchange. Population taken as the object of observation amounted to 148 manufacturing companies in Indonesia Stock Exchange in the period 2007-2010. Determination of the sample was made by applying purposive sampling method in which sampling was taken based on certain criteria. A sample of (n) = 39 companies has been obtained.